Possible treatment failure of artemether-lumefantrine in an Italian traveler with uncomplicated falciparum malaria. - Ernestina Carla Repetto; Claudio Giacomazzi; Antonio Traverso (Mediterranean Journal of Hematology and Infectious Diseases)
Artemisinin-combination therapies (ACTs) are recommended for the treatment of uncomplicated malaria in endemic areas with multidrug resistant Plasmodium falciparum. We report a case of possible artemether-lumefantrine failure in an Italian traveler with uncomplicated P. falciparum malaria imported from Democratic Republic of Congo.